EFFECT DIFFERENCE DOSES OF sGnRH-a + DOMPERIDON HORMONE ON SEMEN VOLUME, QUALITY OF SPERMATOZOA AND FRY HARD LIPPED BARB (Osteochilus hasselti CV) - Muhamad Ambar Budi Hariono; Sukendi '; Nuraini ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted on April-May 2015 at Fish Hatchery andBreeding Laboratory, Faculty Fisheries and Marine Science, University of Riau.The purpose of this research to known the best effect injection difference doses ofsGnRH-a + domperidon hormone on semen volume, quality of spermatozoa andfry hard lipped barb. This research used experimental method with CompletelyRandomized Design (CRD) five treatments and three replications. The treatmentswith injection doses sGnRH-a + domperidon: control (2 ml NaCl physiology 0,9%/kg body weight), P1 (0,3 ml sGnRH-a + domperidon /kg body weight), P2 (0,4ml sGnRH-a + domperidon /kg body weight), P3 (0,5 ml sGnRH-a + domperidon/kg body weight), P4 (0,6 ml sGnRH-a + domperidon /kg body weight). The resultshowed the best effect injection dose is 0,5 ml sGnRH-a + domperidon/kg bodyweight could generate semen volume 0,633 ml, spermatozoa concentrate 1404 x107 cell/ml, motility 71,33%, viability 86,54%. Meanwhile, spawning result withbest effect injection showed fertility rate 81,33%, hatching rate 75,66%, survivalrate of fry 95,1%, growth weight absolute 0,278 g, growth length absolute 1,919cm and growth daily rate 10,17%Key word: Dose sGnRH-a + domperidon, semen volume, quality ofspermatozoa, fry, hard lipped barb (Osteochilus hasselti CV)